PROSEDUR REKRUTMEN DAN SELEKSI KARYAWAN PADA PT. PZ CUSSONS INDONESIA TANGERANG - Irawan, Roy; Wijaya, Darma; kusuma dewi, Intan; Susanti, Herlina (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
With the existence of a system of information technology continues to grow the company to easily create an advertising job vacancies on the internet for simplicity in accelerating the process of recruitment and selection based on procedures that run at PT PZ Cussons Indonesia Tangerang. The methods used in the writing of this qualitative technique is a method of collecting data through observation, interview and documentation. In the procedure of recruitment and selection of employees at PT PZ Cussons Tangerang Indonesia starts from the recipient employee requests a user or supervisor directly, User or supervisor directly fill in the form request inspection employee, based on the organizational structure, the approval of the Director, advertising jobs, screening (filter) CV, calling applicants via e-mail and phone, fill out the application form, interview and psychological test, Direct supervisor and User interviews, medical examinations (medical check up) the working agreement, signature, verification of personal data form, and ends with receiving documents.